2023
DOI: 10.1136/gpsych-2022-101006
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between major depressive disorder and COVID-19

Abstract: BackgroundWe aimed to evaluate whether major depressive disorder (MDD) could aggravate the outcomes of coronavirus disease 2019 (COVID-19) or whether the genetic liability to COVID-19 could trigger MDD.AimsWe aimed to assess bidirectional causal associations between MDD and COVID-19.MethodsWe performed genetic correlation and Mendelian randomisation (MR) analyses to assess potential associations between MDD and three COVID-19 outcomes. Literature-based network analysis was conducted to construct molecular path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In recent years, Mendelian randomization (MR) analysis has been frequently employed to explore causal relationships between various diseases ( Baranova et al , 2023a , 2023b , 2023c ; Cao et al , 2023 ). However, limited data exists regarding the genetic associations between ADHD/ASD and PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Mendelian randomization (MR) analysis has been frequently employed to explore causal relationships between various diseases ( Baranova et al , 2023a , 2023b , 2023c ; Cao et al , 2023 ). However, limited data exists regarding the genetic associations between ADHD/ASD and PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Mendelian randomisation (MR) technique has been widely employed to evaluate causality between risk factors and diseases. [5][6][7] In MR, causality is examined by using germline genetic variants as instruments for quantifying the effect of an exposure on a specific outcome. It was reported that higher EA was associated with an increased risk for bipolar disorder (BD) but a decreased risk for attention-deficit/ WHAT Is ALrEAdY KnoWn on THIs ToPIC ⇒ Educational attainment (EA), intelligence and income are vital psychosocial factors associated with mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the high prevalence, mental illness also increases susceptibility to other diseases, thereby placing a greater burden on society. Recent studies have indicated a genetic link between major depressive disorder (MDD) and coronavirus disease 2019 [ 12 ], as well as between attention deficit hyperactivity disorder (ADHD) and diabetes [ 13 ]. Previous research has identified psychiatric disorders as potential risk factors for TMD [ 14 , 15 ], with multiple observational studies demonstrating a strong association between TMD and mental symptoms like depression and anxiety [ 16 ].…”
Section: Introductionmentioning
confidence: 99%